Estudo da viabilidade técnica de emprego de cimento e emulsão asfáltica para estabilização de bases granulares - Santos, Gabriela Fanck dos (2022)
Quality pavement is of paramount importance for the development and displacement of the population. Several floors have already reached the end of their useful life, requiring maintenance or structural improvement. That said, the milled material from pavement milling has been widely used by several researchers. However, it appears that it is necessary to find an alternative to reuse the recycled pavement, in order to provide economy, sustainability, and feasibility of an application. The study aims to analyze the technical feasibility of mixtures with milled asphalt to replace natural aggregates, stabilized with asphalt emulsion and cement, at different levels, for use in the base layer of asphalt pavements. To this end, laboratory tests of simple compressive strength (RCS), tensile strength by diametral compression (RT), modulus of resilience (MR), and an initial result of the fatigue test were carried out for these mixtures. The tests discussed are conducted from the execution of two models of mixtures, one is called reference (REF), with natural aggregates and the other is with milled material (FP), both matrices framed in the respective granulometric ranges. Therefore, the levels of asphalt emulsion (RL – 1C) applied are 0%, 2% and 3% and the levels of Portland cement (CP – IV32) used are 1% and 3%. The compaction curves were performed using Proctor, in modified energy and the specimens were molded using a Marshall socket and compactor. The initial curing process of the samples occurred in two stages, in a small set of samples the mixtures were cured in a humid chamber and the other set of samples were cured in an oven. The total curing period was 28 days. From the results of resistance and rigidity obtained through the methodological development, it was possible to identify that: in the analysis of the curing process, it influenced the results of RCS and RT, generally presenting the oven as the best way of curing; the increase in the cement and emulsion content brought improvements in strength and stiffness; the mixture with natural aggregates stood out in RCS and MR in relation to those with milled, however, in RT the behavior is opposite; the characteristics of the materials reflect in some aspects, however, a higher density is not a guarantee of better mechanical performance, due to the heterogeneity of the samples; the porosity/volumetric content of cement proved to be efficient to verify the behavior of the studied mixtures; fatigue was satisfactory for cold recycled mixture with asphalt emulsion and Portland cement. It is believed that this can be an excellent technical and economical alternative for the destination of the milled material that is obtained too much in road works.